2004
DOI: 10.1111/j.1572-0241.2004.04110.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Interleukin-8 and Activation of Nuclear Factor Kappa-B in Endoscopy-negative Gastroesophageal Reflux Disease

Abstract: Our results demonstrate enhanced mucosal expression of IL-8 in incipient GERD even without mucosal breaks. NF-kappaB activation may be implicated in the pathogenesis in GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
61
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 31 publications
5
61
0
5
Order By: Relevance
“…These findings are further supported by increased activity of nuclear factor -light-chain-enhancer of activated B cells (NF-B) in the mucosa of GERD patients (55,81). NF-B is a ubiquitous transcription factor regulating proinflammatory responses.…”
Section: Inflammatory Mediators In the Inflamed Esophageal Mucosamentioning
confidence: 60%
See 2 more Smart Citations
“…These findings are further supported by increased activity of nuclear factor -light-chain-enhancer of activated B cells (NF-B) in the mucosa of GERD patients (55,81). NF-B is a ubiquitous transcription factor regulating proinflammatory responses.…”
Section: Inflammatory Mediators In the Inflamed Esophageal Mucosamentioning
confidence: 60%
“…In a Japanese study of patients with nonerosive reflux disease (NERD) with minimal mucosal involvement, as determined by endoscopy, IL-8 mRNA levels were increased compared with NERD patients with no mucosal involvement and with controls (63). After successful treatment with PPIs or Nissen fundoplication, IL-8 levels declined (55,83,138). High mucosal IL-8 levels predicted an increased relapse rate for GERD within 3 years, indicating a potential prognostic role for this cytokine (53).…”
Section: Inflammatory Mediators In the Inflamed Esophageal Mucosamentioning
confidence: 99%
See 1 more Smart Citation
“…20 The relative IL-8 mRNA expression are significantly higher in esophageal mucosa of non-erosive reflux disease than controls, and lansoprazole treatment significantly reduces IL-8 mRNA expression levels. 21 However, no reports have described the relationship between circulating cytokines and reflux esophagitis, although several studies have shown the association between circulating cytokines and Barrett's esophagus. 22 In our study, circulating inflammatory cytokines such as IL-1, were increased in reflux esophagitis with adjusted analysis, even though its effect on reflux esophagitis was abolished with additional adjusted analysis for visceral fat and BMI.…”
mentioning
confidence: 99%
“…Several studies have suggested that mucosal cytokines are increased in GERD. 20,21 In 22 patients with non-erosive reflux disease, mucosal levels of cytokines (IL-8, IL-1, and CCL5) had a positive with recurrent reflux symptoms. 20 The relative IL-8 mRNA expression are significantly higher in esophageal mucosa of non-erosive reflux disease than controls, and lansoprazole treatment significantly reduces IL-8 mRNA expression levels.…”
mentioning
confidence: 99%